KOTA, RUANG, DAN POLITIK KESEHARIAN: Produksi dan Konsumsi Ruang Bersenang-senang dalam Geliat Yogyakarta - Ali Minanto (Program Studi Ilmu Komunikasi, 2018)
The city grows with its paradox. On the one hand, the city offers dreams, into magnetic spaces that suck anyone to be absorbed in it. However, on the other hand, it becomes the engine to crush all desires and imagination about beauty, well-being, and prosperity that live in the minds of people. Yogyakarta, a city that has many predicates, continues to change. As a space where many different identities live together, Yogyakarta begins to improve by presenting new consumerism sites that have the potential to get rid of public spaces. Reduction of public space stimulates the presence of alternative spaces as a new public space. It will be a destination for citizen escapism to find space of enjoyment. This article wants to see how the space of enjoyment as alternative spaces in Yogyakarta are produced and consumed by the citizens of Yogyakarta.Keywords: City, Yogyakarta, Space of Enjoyment